2016
DOI: 10.1128/jcm.01467-16
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vibrio cholerae Strains Isolated from the Nigerian Cholera Outbreak in 2010

Abstract: We examined clinical samples from Nigerian patients with acute watery diarrhea for Vibrio cholerae during the 2010 cholera outbreak. A total of 109 suspected isolates were characterized, but only 57 V. cholerae strains could be confirmed using multiplex real-time PCR as well as rpoB sequencing and typed as V. cholerae O:1 Ogawa biotype El Tor. This finding highlighted the need for accurate diagnosis of cholera in epidemic countries to implement life-saving interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…cholerae O1 and pathogens other than vibrios were detected. The frequency and diversity of other pathogens associated with diarrhoea in Ghana, concurs with similar reports from Nigeria, Bangladesh, Tanzania and Sierra Leone [ 28 31 ]. This underscores the need to scale up laboratory-based surveillance of diarrhoeal diseases so that accurate identification of the specific aetiology of diarrhoeal diseases can be made using the Integrated Disease Surveillance and Response (IDSR) approach to effectively identify causative agent to enhance appropriate therapy.…”
Section: Discussionsupporting
confidence: 88%
“…cholerae O1 and pathogens other than vibrios were detected. The frequency and diversity of other pathogens associated with diarrhoea in Ghana, concurs with similar reports from Nigeria, Bangladesh, Tanzania and Sierra Leone [ 28 31 ]. This underscores the need to scale up laboratory-based surveillance of diarrhoeal diseases so that accurate identification of the specific aetiology of diarrhoeal diseases can be made using the Integrated Disease Surveillance and Response (IDSR) approach to effectively identify causative agent to enhance appropriate therapy.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, conventional PCRs for the determination of serotype serogroup-specific gene rfb were performed to confirm the identification of non-O:1/non-O:139 V. cholerae strains. Primers and probes were used as previously described [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…From samples collected during the 2010 cholera epidemic in Nigeria, Oyedeji et al 34 identified the classical biotype while Dupke et al 35 the El Tor biotype, thus making it challenging to infer about the prevailing biotype in the present epidemic. Nonetheless, the El Tor biotype as identified by Dupke et al 35 may be more likely, given the identification of multidrug-resistant atypical El Tor strains from samples collected during the same epidemic by Marin et al 36 The CFR of 3.52% reported for the cholera epidemic is about two times as high as the 1.90% recorded in 2018 10 but lower than the 5.1% in 2010. 11 This could be explained by differences in the denominator population across the various epidemics.…”
Section: Interpretation Of Key Findingsmentioning
confidence: 99%